New detrital zircon U-Pb ages on Neoproterozoic Tandilia sequences, Río de la Plata craton, Argentina - Cingolani, Carlos Alberto (2010)
The geological evolution of Tandilia comprises mainly a juvenile igneous-metamorphic Paleoproterozoic basement named Buenos Aires Complex, which is covered by thin Neoproterozoic to Early Paleozoic sedimentary units which displays sub horizontal bedding (Fig. 1). This work is related to introduce the new detrital zircon U-Pb ages from two siliciclastic Neoproterozoic sequences called Villa Mónica and Cerro Negro Formations from the Barker region, and offer the comparison provenance analysis of these data with previous contributions in a paleogeographic interpretation.